Analisis Kinerja Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Maria Salda Tangke Bandaso; Agustinus Mantong; Helba Rundupadang (Universitas Kristen Indonesia Toraja, 2023)
Maria Salda Tangke Bandaso, 2023 Analysis of Financial Performance in Manufacturing Companies Listed on the Indonesian Stock Exchange. This study aims to identify and analyze the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. This type of research is descriptive quantitative research, descriptive quantitative research is the calculation of data in the form of annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange. The type of data used is secondary data in the form of data in the form of documents obtained by the official IDX link (www.idx.co.id). From the results of the research, the results obtained are 1) based on the current ratio or the current ratio of the financial performance of companies listed on the IDX that are sampled to get good/very good criteria 2) based on quick ratios or quick ratios of the financial performance of companies listed on the IDX that are sampled to get good/very good criteria 3) based on cash ratios or cash ratios of companies listed on the IDX that are sampled to get very good criteria